2002
DOI: 10.1002/poc.528
|View full text |Cite
|
Sign up to set email alerts
|

Study of inclusion complexes of acridine with β‐ and (2,6‐di‐O‐methyl)‐β‐cyclodextrin by use of solubility diagrams and NMR spectroscopy

Abstract: Previous molecular modeling studies, in our laboratory, have shown that some esters of type RCOO(CH2) nC5H5N+Cl− are potentially active against Alzheimer's disease. We have also demonstrated that acridine, which has strong anticholinesterase activity appears to be a suitable R substituent. The main obstacle to the possible pharmaceutical application of these compounds is their limited solubility in water, which is due to the poor aqueous solubility of acridine itself (0.26 mM). Inclusion complexation with cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…According to the literature, phase solubility analysis is one of the preliminary requirements for developing a drug/cyclodextrin inclusion complex as it permits an evaluation of the affinity between the drug molecule and cyclodextrin (21). Many researchers have used this approach to determine the molar ratio in which a drug can form a complex with cyclodextrins (11)(12)(13)(14). However, the phase solubility profiles do not demonstrate the formation of inclusion complexes; they only describe how the increasing cyclodextrin concentration influences drug solubility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, phase solubility analysis is one of the preliminary requirements for developing a drug/cyclodextrin inclusion complex as it permits an evaluation of the affinity between the drug molecule and cyclodextrin (21). Many researchers have used this approach to determine the molar ratio in which a drug can form a complex with cyclodextrins (11)(12)(13)(14). However, the phase solubility profiles do not demonstrate the formation of inclusion complexes; they only describe how the increasing cyclodextrin concentration influences drug solubility.…”
Section: Discussionmentioning
confidence: 99%
“…A greater number of reports mentioned the use of cyclodextrins in the formation of inclusion complexes with hydrophobic drugs, including acridine derivatives, for enhancement of their solubility (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] It has also been shown that cyclodextrins are, like noncyclic oligosaccharides, able to form non-inclusion complexes. [8][9][10][11][12][13] For example, Gabelica et al 8,9 have reported that a-cyclodextrin forms both inclusion and noninclusion complexes with a,o-dicarboxylic acids and that the two types of complexes coexist in aqueous solutions. By comparing a-cyclodextrin complexes with those of maltohexaose, a linear analog of a-cyclodextrin, the authors were able to show that the 1:1 a,o-dicarboxylic acid/a-cyclodextrin complexes are mainly inclusion complexes whereas 2:1 complexes, formed by additional complex formation between a given acid and a 1:1 complex, are non-inclusion complexes.…”
Section: Introductionmentioning
confidence: 97%
“…Any two protons that are located within 0.4 nm in space can produce a nuclear overhauser effect (NOE) cross-correlation in NOE spectroscopy (NOESY) or rotating-frame NOE spectroscopy (ROESY) [23,24]. In the structure of β-CD the H3 and H5 protons are situated inside the conical cavity, particularly, the H3 are placed near the wider rim while H5 are placed near the narrower rim, the other H1, H2 and H4 protons are located at the exterior of the β-CD molecule (Figure 3) [25,26].…”
Section: D Nmr Spectra Analysismentioning
confidence: 99%